Screening of antagonistic bacterial isolates from hives of Apis cerana in Vietnam against the causal agent of American foulbrood of Honey Bees, Paenibacillus larvae - Sasiprapa Krongdang (2018)
© 2018, Chiang Mai University. All rights reserved. American foulbrood (AFB) is a virulent disease of honey bee brood caused by the Gram-positive, spore-forming bacterium; Paenibacillus larvae. In this study, we determined the potential of bacteria isolated from hives of Asian honey bees (Apis cerana) to act antagonistically against P. larvae. Isolates were sampled from different locations on the fronts of A. cerana hives in Vietnam. A total of 69 isolates were obtained through a culture-dependent method and 16S rRNA gene sequencing showed affiliation to the phyla Firmicutes and Actinobacteria. Out of 69 isolates, 15 showed strong inhibitory activity against P. larvae; Bacillus pocheonensis (VN101) showed the largest zone of inhibition (26 ± 1 mm). In this study, the diversity and richness of antagonistic isolates indicated that Bacillus spp. are the most promising as inhibitors of P. larvae. These finding suggested that certain bacterial isolates can act as antagonist to control P. larvae and may have other biotechnological applications.